IMPROVING STUDENTS' LEARNING OUTCOMES IN MATHEMATICS THROUGH THE CTL APPROACH IN CLASS VII SMP NEGERI 8 GORONTALO (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
To solve the problems that have been formulated by researchers using the CTL (Contextual teaching and Learning) learning model in Mathematics in class VII SMP Negeri 8 Gorontalo" in order to increase student activity and learning outcomes, researchers choose alternative problem solving using the CTL (Contextual teaching and learning) include: 1. (Constructivism) Developing students' thinking to carry out more meaningful learning activities whether by working alone, finding themselves, and constructing new knowledge and skills they have. 2. (Questioning) Develop students' curiosity by raising questions. 3. (Learning community) Creating a learning community, such as through group discussion activities, question and answer, and so on. According to researchers, using CTL (Contextual Teaching and Learning) can increase student learning activities and outcomes.